Pembelajaran Mitigasi Bencana Banjir Pada Siswa SMPN 8 Kubu Raya - Sukal Minsas (Journal of Community Development, 2024)
Floods are a serious threat in many regions in Indonesia and have a significant impact on society and the environment, either due to the rainy season or due to ROB floods caused by strong sea tides and large waves, especially in the coastal areas of West Kalimantan. Learning flood disaster mitigation material at school age from an early age is very necessary as a provision for students in implementing the steps or efforts that need to be taken when there is a flood disaster. This community service activity aims to educate students at SMPN 8 Kubu Raya which is located in the coastal area of ​​Kakap Kubu Raya District, regarding flood disaster mitigation. This activity was attended by 40 students from class 2 representatives, using educational lecture learning methods and watching YouTube content together. An effective learning approach involves the use of a variety of resources, including instructional videos. The students' interest during this activity was shown by group discussion activities which took place enthusiastically, a flood disaster simulation using animation in YouTube video content was also an effective method in increasing students' understanding and involvement. Students' active involvement in flood disaster mitigation learning activities can increase their awareness of the importance of preparedness and preventive measures. Based on the evaluation of educational activities carried out by the activity implementing team through questions given regarding educational lecture material and watching YouTube animation videos, it shows that randomly selected participants were able to respond with appropriate and quick answers to these questions.